Rice stripe virus p2 protein interacts with ATG5 and is targeted for degradation by autophagy - Zhang, Xiangxiang; Wan, Qionglian; Rui, Penghuan; Lu, Yuwen; Sun, Zongtao; Chen, Jianping; Wang, Yunyue; Yan, Fei (Frontiers in Microbiology, 2023)
Autophagy can be induced by viral infection and plays antiviral roles in plants, but the underlying mechanism is not well understood. In our previous reports, we have demonstrated that the plant ATG5 plays an essential role in activating autophagy in rice stripe virus (RSV)-infected plants. We also showed that eIF4A, a negative factor of autophagy, interacts with and inhibits ATG5. We here found that RSV p2 protein interacts with ATG5 and can be targeted by autophagy for degradation. Expression of p2 protein induced autophagy and p2 protein was shown to interfere with the interaction between ATG5 and eIF4A, while eIF4A had no effect on the interaction between ATG5 and p2. These results indicate an additional information on the induction of autophagy in RSV-infected plants.